PERLINDUNGAN DAN PENGAKUAN HAK ULAYAT MASYARAKAT ADAT BIAK PAPUA - Dicky Eko Prasetio (Sabtida, 2024)
The Biak Customary Law Community in Papua has unique customary rights, particularly with regard to water aspects. The recognition and protection of the Biak Customary Law Community encounters problems when it is compared to the spaceport in Papua which is in the territory of the Biak Customary Law Community. Apart from that, from a juridical perspective, there is also a legal vacuum regarding regulations related to the Biak Customary Law Community, especially in Biak Numfor Regency. The legal issues analyzed in this study are related to the legal vacuum regarding the recognition and protection of the customary rights of the Biak Customary Law Community. This research is a normative legal research that focuses on the analysis of legal issues in the form of a legal void in the recognition and protection of the Biak Customary Law Community by using a concept and statutory approach. The results of the study confirm that the legal implication of the existence of a regulatory legal vacuum regarding the recognition and protection of the Biak Indigenous People, Papua, namely customary rights, traditions and local wisdom has the potential to no longer be enforceable due to the existence of a spaceport project in Biak. Future arrangements related to efforts to recognize and protect the Biak Customary Law Community, especially in terms of their customary rights, namely through the establishment of a Regional Regulation of the Biak Numfor Regency related to the Biak Customary Law Community, Papua and at the national level need to ratify the Indigenous Law Community Bill. Keywords: Ulayat Rights, Biak Customary Law Society, Recognition and Protection of Customary Law Communities.